Surface Engineering Enabled Capacitive Gas‐Phase Water Molecule Sensors in Carbon Nanodots - Qin, Jin‐Xu; Shen, Cheng‐Long; Zhang, Wu‐You; Deng, Yuan; Lai, Shou‐Long; Lv, Chao‐Fan; Liu, Hang; Zhang, Ying‐Jie; Liu, Lan; Li, Lei; Yang, Xi‐Gui; Shan, Chong‐Xin (Advanced science, 2025)
Gas‐phase water molecule sensors are essential in scientific, industrial, and environmental applications, playing a crucial role in ensuring human safety, monitoring pollution, and optimizing processes. However, developing gas‐phase water sensors with high sensitivity remains a significant challenge. Herein, the effect of molecular adsorption on capacitive response is explored, and a facile surface engineering strategy to achieve sensitive carbon nanodots (CDs)‐based sensors for H2O is demonstrated.hydrophilic raw precursor is utilized to prepare the hydrophilic CDs and further employ these CDs as active media in the capacitive sensors, demonstrating how surface adsorption influences the capacitive response to H2O molecules. By applying surface engineering, the molecular affinity potential of CDs is regulated, resulting in sensors that exhibit a broad detection range from 11% to 98% relative humidity (RH), with a remarkable sensitivity of 3.3 × 105 pF/RH and an impressive response of 1.8 × 108% at 98% RH. These CDs‐based sensors present great potential for applications in respiratory monitoring, information exchange, contactless recognition of finger trajectories, etc. The findings unveil the unique influence of molecular affinity on capacitive response, opening new avenues for the design and applications of highly sensitive molecular sensors. A surface engineering strategy is developed to tune the molecular affinity of carbon nanodots (CDs), leading to capacitive sensors with an impressive detection range from 11% to 98% relative humidity (RH). These sensors demonstrate high sensitivity, with 3.3 × 105 pF/RH, and an exceptional response of 1.8 × 108 % at 98% RH. This approach unlocks new possibilities for CDs in practical applications, such as respiratory monitoring, contactless recognition of finger trajectories, and environmental sensing. The findings offer significant potential for future molecular sensor designs and wide‐ranging industrial applications.